Crack identification in multiple cracked beams made of functionally graded material by using stationary wavelet transform of mode shapes - Lien, Tran Van; Duc, Ngo Trong (Vietnam Journal of Mechanics, 2019)
This paper presents crack identification in multiple cracked beams made of functionally graded material (FGM) by using stationary wavelet transform (SWT) of mode shapes and taking into account influence of Gaussian noise. Mode shapes are obtained from multiple cracked FGM beam element and spring model of cracks. The theoretical development was illustrated and validated by numerical examples. The investigated results show that crack identification method by using SWT of mode shapes is efficient and realizable.